Standar Operasional Prosedur (SOP) Kalibrasi Arah Kiblat Masjid di Era Digital - I . Ismail (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2019)
This paper tries to explain the ideal standard in conducting calibration in Qibla direction by referring to social problems in the digital era. In the digital era, a reference in carrying out the Qibla direction calibration tasks must be truly socially and scientifically accountable, both in using guidelines or standard operating procedure (SOP), as well as calibration minutes made as a placeholder's grip on Qibla direction calibration. . New problems can occur after the calibration of the Qibla direction is carried out, such as the rejection of the results of the calibration of the Qibla direction by a number of mosque worshipers which can lead to religious splits, most of these rejections come from the social and scientific dimensions that have not been fully fulfilled when the calibration was carried out. To avoid or minimize the occurrence of Muslim comflications after calibrating the direction of the mosque's Qibla, these two elements must be truly considered, namely the element of social and scientific elements